Oligostilbenes from the leaves of Gnetum latifolium and their biological potential to inhibit neuroinflammation - Cho, Hyo Moon; Thi Kim Quy Ha; Ha Thanh Tung Pham; An, Jin-Pyo; Huh, Jungmoo; Lee, Ba-Wool; Lee, Hee Ju; Oh, Won Keun (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Oligostilbenes are polyphenol oligomers derived from resveratrol and are commonly produced by members of the Gnetaceae family, and many researchers have focused on their anti-inflammatory activities. The EtOAc fraction of a Gnetum latifolium extract showed inhibitory activity against neuroinflammation induced by the transfection of A beta(1-42) into microglial BV-2 cells. The bioassay-guided isolation of the 70% EtOH extract of this plant resulted in three previously undescribed resveratrol oligostilbenes and ten known stilbene derivatives. The structures of the isolated compounds were established based on extensive NMR spectroscopic analysis. The absolute configurations of the three undescribed compounds were confirmed by comparison with available compounds with known stereochemistry and by ECD calculations and molecular modelling. Latifoliols A and B are the first reported oligostilbenes with a bridged 3-oxabicyclo[3.3.0]octane moiety, and latifoliol C was formed by the condensation of gnemontanin G with oxyresveratrol. Moreover, the hypothetical biogenetic pathway of latifoliols A, B and C was proposed. The potential anti-inflammatory activities of the thirteen isolated compounds were tested by measuring their effect on the secreted NO concentrations induced by transfection with plasmids expressing the A beta(1-)(42) gene in the BV-2 cell line. Interestingly, cis- and trans-shegansu B and latifolol, whose structures contained double bonds, strongly inhibited NO secretion in BV-2 cells, supporting the double binding effect of the stilbene derivative on inhibitory activity.
Keywords: STILBENE DERIVATIVES; DIMERIC STILBENE; RESVERATROL; RESTRICTION; SIRTUINS; MODEL